Assessment of the muscle architectural parameters in skill and nonskilled Karate players - Adibian, M.; Ilbeigi, S.; Ehsanbakhsh, A. (Journal of Advanced Sport Technology, 2018)
The aim of this study was to assess the muscle architectural parameters in skill and non-skilled Karate players. Material and method: For this purpose 30 Karate players were assigned into skill (mean age of 22.03 ± 1.25 years, mean height of 1.76 ± 3.47 m and mean weight of 63.0 ± 1.01 kg) and non-skilled (mean age of 20.08 ± 2.04 years, mean height of 1.73 ± 1.44 m and mean weight of 59.01 ± 3.25 kg) groups. Muscle thickness, pennation angle and fascicle length in 50%, 60% and 70% of biceps and triceps length sites was measured using ultrasonography images. Independent t-test was used for data analysis. Result:The results of independent sample t-test showed there was a significant differences between Muscle thickness of triceps in skill and non-skilled Karate players (p 0.05). There was also a significant differences between pennation angle of triceps in skill and non-skilled Karate players (p 0.05). Other results of this study showed there was a significant differences between fascicle length of triceps and also between muscle thicknesses of biceps in two groups (p 0.05). Conclusion: it seems practicing karate at high levels can cause changes in muscle architecture parameters and with impress some parameters associated with length and muscle tension, provide areas for improving motor function in karate special techniques. Keywords: Muscle pennation, Karate players, Muscle architecture, Muscle thickness, Fascicle length.